Search for contact interactions in dimuon events from pp collisions at √s=7TeV with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbi, E; Acharya, B; et al. (2011)
A search for contact interactions has been performed using dimuon events recorded with the ATLAS detector in proton-proton collisions at √s=7TeV. The data sample corresponds to an integrated luminosity of 42pb-1. No significant deviation from the standard model is observed in the dimuon mass spectrum, allowing the following 95% C.L. limits to be set on the energy scale of contact interactions: Λ>4.9TeV (4.5 TeV) for constructive (destructive) interference in the left-left isoscalar compositeness model. These limits are the most stringent to date for μμqq contact interactions. 2011 American Physical Society.